2009
DOI: 10.1007/s00384-009-0725-z
|View full text |Cite
|
Sign up to set email alerts
|

Elevated expressions of MMP7, TROP2, and survivin are associated with survival, disease recurrence, and liver metastasis of colon cancer

Abstract: We conclude that elevated survivin, MMP7, and TROP2 expression levels are related to decreased survival. In addition, elevated MMP7 and TROP2 expression levels are predictors of disease recurrence and liver metastasis, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
131
2
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(150 citation statements)
references
References 57 publications
13
131
2
4
Order By: Relevance
“…In the current study we found that MMP-7 was overexpressed in 38.8% of CRCs and this positive rate is comparable with previous reports of 30% to 46% [15] [17] [30] [32]. In a recent study with a larger sample size of 620 cases, Fang et al reported MMP-7 immunopositivity in 88.8% of the cancer [33]. Roca and co-investigators demonstrated 81.7% of 60 CRC tumors were positive for MMP-7 [34].…”
Section: Discussionsupporting
confidence: 91%
“…In the current study we found that MMP-7 was overexpressed in 38.8% of CRCs and this positive rate is comparable with previous reports of 30% to 46% [15] [17] [30] [32]. In a recent study with a larger sample size of 620 cases, Fang et al reported MMP-7 immunopositivity in 88.8% of the cancer [33]. Roca and co-investigators demonstrated 81.7% of 60 CRC tumors were positive for MMP-7 [34].…”
Section: Discussionsupporting
confidence: 91%
“…MMP7 was determined to be up-regulated in cirrhotic nodules (potential precursors of HCC), compared with normal liver, as well as in HCC (71). Furthermore, elevated MMP7 expression is correlated with decreased survival and increased recurrence and liver metastasis of colon cancer (72) and pancreatic carcinoma (73). Most importantly, MMP7 was demonstrated to promote in vitro invasiveness of cancer cells of the stomach, colon, and pancreas (reviewed in Ref.…”
Section: Table 3 Distribution Of Identified Mir-122 Targets Accordingmentioning
confidence: 99%
“…Fang ve arkadaşlarının yaptığı bir başka çalışmada ise tumor dokusunda matrix metalloproteinaz-7 (MMP7) over ekspresyonunun karaciğer metastazını predikte etmede etkili olabileceği gösterilmiştir (OR 6,7, p=0,003) (17). Bu çalışmaların tamamında olası biyolojik markerların tamamı tümör dokusunda bakılmış olup kullanımları kısıtlı kalmıştır, bu sebeple tanı anında karaciğer metastazını predikte edebilecek kolay ulaşılabilir ve daha ucuz belirteçler gerekmektedir.…”
Section: Gereç Ve Yöntemunclassified